Wealth Taxes on Individuals: An International Comparative Study - Estelle Abrahams; Suzette Bosman (Yayasan Ilomata, 2023)
Citizens contribute to the economy by creating wealth for themselves and in the way they use their assets. How assets, especially capital assets, are employed attracts tax and this influences how assets are used. In South Africa, tax policy is one of the drivers in the decisions that individuals make regarding the use or disposal of their assets. Wealth taxes are levied to address income disparities and mostly affect capital assets when they change ownership. This study compares developed and developing countries’ tax policies that impact capital assets when they are transferred or disposed of. The financial impact from using one’s assets drives economic participation. Previous studies found that tax policy is influential in economic participation. A literature study was performed analysing wealth taxes, academic literature and legislation and incorporated a case study to illustrate the tax consequences of capital assets changing ownership in Namibia, South Africa, India and Australia. The study found that, compared to the other countries, South Africa taxes capital transfer both upon change of ownership by way of sale, donation and death of the owner. This study makes a novel contribution to the understanding of and development of improved and internationally comparable wealth tax legislation to address the wealth tax consequences of asset transactions in South Africa.